POSITION AND VELOCITY ESTIMATION IN THE VISUAL CORTEX - Ghosh, Bijoy K.; Nenadic, Zoran (IFAC Proceedings Volumes, 2002)
Using tools from dynamical systems theory and systems identification theory we develop the study of primitives for human motion which we refer to as movemes. We introduce basic definitions of dynamical independence of linear time-invariant dynamical systems (LTI) and segmentability of signals and we develop classification and segmentation algorithms for two dimensional motions. We test our ideas on data sampled from four human subjects who were engaged in a simple real-life activity including two movemes. Our experiments show that we are able to distinguish between the two movemes and recognize them even when they take place in an activity containing more than one moveme.